Biochemical markers of cholestasis in rats with acetaminophen-induced intoxication after partial hepatectomy - Kopylchuk, Halyna; Nykolaichuk, Ivanna; Ursatyi, Mariia (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):241